2023
DOI: 10.1002/mgg3.2280
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent human 16p11.2 microdeletions in type I Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome patients in Chinese Han population

Kaizhen Su,
Han Liu,
Xiaoqun Ye
et al.

Abstract: BackgroundsMayer‐Rokitansky‐Küster‐Hauser (MRKH) syndrome, a severe congenital malformation of the female genital tract, is a highly heterogeneous disease which has no clear etiology. Previous studies have suggested that copy number variations (CNVs) and single‐gene mutations might contribute to the development of MRKH syndrome. In particular, deletions in 16p11.2, which are suggested to be involved in several congenital diseases, have been reported in Chinese type II MRKH patients and European MRKH patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In 2011, Nik-Zainal et al (71) reported four cases with recurrent deletions of 16p11.2 and suggested TBX6, previously implicated in paraxial mesoderm development (131), as a candidate gene. To date, a large number of cases have been identified with both deletions (30,(71)(72)(73)(74)(75)(76)(77)(78)(79) and TBX6 sequence variants (72,75,103,105,111,112). The 16p11.2/TBX6 locus is also associated with congenital scoliosis (132).…”
Section: P112 Deletions and Tbx6mentioning
confidence: 99%
“…In 2011, Nik-Zainal et al (71) reported four cases with recurrent deletions of 16p11.2 and suggested TBX6, previously implicated in paraxial mesoderm development (131), as a candidate gene. To date, a large number of cases have been identified with both deletions (30,(71)(72)(73)(74)(75)(76)(77)(78)(79) and TBX6 sequence variants (72,75,103,105,111,112). The 16p11.2/TBX6 locus is also associated with congenital scoliosis (132).…”
Section: P112 Deletions and Tbx6mentioning
confidence: 99%